280 The Effect of Bromocriptine Mesylate and Heat Stress on Innate and Adaptive Immune Function in Beef Cattle. (21st September 2022) - Zeltwanger, Joshua M; Bailey, Eric; Spiers, Don; Petzel, Emily; Nelson, Benjamin; Brake, Derek
Abstract: Injection of bromocriptine mesylate has been used to mimic the symptoms of tall fescue toxicosis in beef cattle. Twelve steers (351 ± 11.82 kg) were used to investigate the effect of bromocriptine mesylate and heat stress on serum prolactin, rectal temperature, respiration rate, and innate/adaptive immune function. Steers were randomly assigned to receive an injection of saline (CON) or bromocriptine mesylate (BROMO; 0.1mg/kg BW) every three days. Animals were housed for 22 d in the Brody Climatology Laboratory at thermoneutrality (TN; 19.5±0.26°C; 10-d) before transitioning (2-d) to heat stress (HS; 27.2±0.26°C nighttime, 34.5±0.26°C daytime; 10-d). Cattle were fed 1.8% of BW (DM-basis) daily across two feedings. Rectal temperatures and respiration rates were measured daily at 0600, 0900, 1500, and 1800 h. Serum and plasma were harvested from blood collected on d 1, 9, and 21 (9 th d of thermoneutrality and heat stress, respectively) and analyzed for prolactin and cytokines. Dry-matter intake was not affected by treatment (P=0.52) or temperature (P=0.78). Prolactin concentrations decreased (P=0.02) throughout the trial and decreased (P< 0.01) with BROMO. Rectal temperature and respiration rate were greater (P< 0.01) for BROMO during TN and HS. Rectal temperature and respiration rate were increased (P< 0.01) during HS. Pro-inflammatory cytokine (TNF-α, IFN-α, IFN-γ, IL-1α, IL-1β, IL-17, and IL-18) concentrations were greater (P< 0.01) for BROMO steers than CON. Heat stress increased (P< 0.01) pro-inflammatory cytokines with the exception of IL-18 (P=0.98) regardless of treatment. Anti-inflammatory cytokines (IL-13, IL-1-F5, IL-21, IFN-β, LIF) were decreased (P< 0.07) for BROMO steers with the exception of IL-10 (P=0.58). Regardless of treatment IL-13, IL-21, IL-10, and LIF concentrations were greater (P< 0.05) during HS. These results demonstrate that bromocriptine mesylate successfully mimicked the symptoms of fescue toxicosis. Innate and adaptive immune responses were influenced by treatment and temperature, potentially affecting beef cattle immune competency.